Dampak Globalisasi dalam Perkembangan serta Kemajuan Hubungan Kerjasama Antara Indonesia dan Jepang - Alvin Pratama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2023)
Globalization shows the process of increasing interconnectedness and interdependence of world cultures and economies. Globalization targets all aspects of life, including cooperative relations between countries in the world. Indonesia and Japan have had close cooperative relations in recent decades. This research aims to identify the impact of globalization on the dynamics of cooperative relations between Indonesia and Japan. The research method used is a qualitative descriptive method through literature study. Based on the research results, it was concluded that the impact of globalization plays a significant role in the cooperative relations between Indonesia and Japan. The two countries collaborate through various sectors, such as economics, employment, politics, education, science and technology, tourism, culture, disaster mitigation and military.